2017
DOI: 10.1128/mbio.01189-17
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spleen-Induced Fimbria Production in Recombinant Attenuated Salmonella enterica Serovar Typhimurium Vaccine Strains

Abstract: Salmonella enterica serovar Typhimurium genome encodes 13 fimbrial operons. Most of the fimbriae encoded by these operons are not produced under laboratory conditions but are likely to be synthesized in vivo. We used an in vivo expression technology (IVET) strategy to identify four fimbrial operons, agf, saf, sti, and stc that are expressed in the spleen. When any three of these operons were deleted, the strain retained wild-type virulence. However, when all four operons were deleted, the resulting strain was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…As for Lpf fimbriae, little is known about Sti fimbriae. A study by P. Laniewski et al (46) revealed the involvement of Sti, Saf, Stc and curli fimbriae in murine infection model. Deletion of all four fimbrial operons resulted in a strain attenuated in a murine infection model, but if only one operon was deleted, no effect was observed.…”
Section: Discussionmentioning
confidence: 99%
“…As for Lpf fimbriae, little is known about Sti fimbriae. A study by P. Laniewski et al (46) revealed the involvement of Sti, Saf, Stc and curli fimbriae in murine infection model. Deletion of all four fimbrial operons resulted in a strain attenuated in a murine infection model, but if only one operon was deleted, no effect was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, Saf fimbriae were reported to be involved in biofilm formation and in binding to porcine intestine cells IPEC-J2 cells (49). In addition, expression of Saf fimbriae were only observed during infection of murine spleen (50). Genes of the saf operon are often pseudogenes in host-restricted Salmonella serovars (Typhi, Paratyphi and Gallinarum) (10), indicating their potential contribution in STM in dispersal by farm animals and newly investigated environmental routes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Heidelberg [29] while it has been found important for pathogenesis in other serotypes such as Salmonella ser. Typhimurium [32]. Transcription of saf fimbrial genes has been found in blood samples from patients infected with Salmonella ser.…”
Section: Antimicrobial Resistance Gene Profiling Of Salmonella Ser Hmentioning
confidence: 99%